Germination and initial growth of bell pepper and lettuce inoculated with rhizobia and molecular identification of the strains (Bioagro, 2020)
The seeds of some vegetables of high consumption by the Venezuelan population have a low percentage and delay in germination. In this research we evaluated the effect of ten indigenous rhizobial isolates on the germination and growth of bell pepper (Capsicum annuum L.) and lettuce (Lactuca sativa L.) during seedling stage to produce more vigorous plants. One hundred seeds were planted/treatment in triplicate and inoculated with the bacterial cultures (1x108 cel∙mL-1) plus a non-inoculated control, recording the germination during 8 days. Fifteen seedlings were transplanted/treatment to propagation trays with an inert sterile substrate, reinoculated and maintained for 30-45 days, to evaluate the effect on growth. The results were analyzed by Anova and compared with the control. The isolates RmBorbollon and ME01 were the most efficient to promote germination (P≤0,05) in bell pepper. No effect was found for lettuce germination. The isolates ME01 and Med increased significantly (P≤0,05) most growth variables in bell pepper and just a few in lettuce, which suggests some specificity of action  between microorganisms and  plant species. The strains were identified as belonging to the genera Ochrobactrum, Bradyrhizobium and Pseudomonas. It is concluded that these isolates, at exerting their promoter effect, may constitute promising strains for the formulation of biofertilizers.
Keywords: Bioinoculants; Capsicum annuum; gen 16S; Lactuca sativa; PGPR